Muscular dystrophy in girls with X;autosome translocations. Issue 6 (December 1986) - Boyd, Y; Buckle, V; Holt, S; Munro, E; Hunter, D; Craig, I
Abstract : Twenty known cases of X;autosome translocations with breakpoints at Xp21 associated with Duchenne or Becker muscular dystrophy in girls are reviewed. The variable severity described for different persons may reflect differences in X inactivation or in the nature of the genomic target disrupted. High resolution cytogenetic studies on 12 cases indicate breakpoints on the X chromosome at Xp21.1 or Xp21.2. Translocation chromosomes from several of these cases have been isolated in human/mouse somatic cell hybrids. Molecular heterogeneity in the breakpoint positions has been established by probing DNA from these hybrids with a range of cloned sequences known to be located within, or closely linked to, the Duchenne region. The minimum separation between the most distal and the most proximal breakpoints is 176 kb suggesting that, if a single gene is involved, it must be large. Alternatively, the translocations may affect different genes, or confer alterations to regulatory sequences which operate at a distance.